HOW RICE SEED FARMERS PARTICIPATE IN ADDITIONAL PARTNERSHIP PROGRAM: EXPERIENCE FROM ACEH-INDONESIA - Setia Budi; Jamilah; Eva Wardah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the level of farmer participation in the agricultural extension partnership program in North Aceh and Pidie Jaya districts, Aceh-Indonesia. This is a case study involving 187 rice seed farmers as research samples. Data was measured and analyzed using a Likert Scale. The results showed that the level of farmer participation in the agricultural extension partnership program was good with an index value of 79.16%. Sequentially the response of farmers' involvement in agricultural activities (87.37%), provision of production facilities (84.24%) and program planning (80.14) were in very good category. The involvement of farmers in product processing (76.26%), program evaluation (74.69%) and product marketing (72.24%) is included in the good category.